The Glucagon-Like Peptide 1 Receptor Agonist Exenatide Inhibits Small Intestinal Motility, Flow, Transit, and Absorption of Glucose in Healthy Subjects and Patients With Type 2 Diabetes: A Randomized Controlled Trial - Thazhath, Sony S.; Marathe, Chinmay S.; Wu, Tongzhi; Chang, Jessica; Khoo, Joan; Kuo, Paul; Checklin, Helen L.; Bound, Michelle J.; Rigda, Rachael S.; Crouch, Benjamin; Jones, Karen L.; Horowitz, Michael; et al. (Diabetes (New York, N.Y.), 2016)
The short-acting glucagon-like peptide 1 receptor agonist exenatide reduces postprandial glycemia, partly by slowing gastric emptying, although its impact on small intestinal function is unknown. In this study, 10 healthy subjects and 10 patients with type 2 diabetes received intravenous exenatide (7.5 μg) or saline (−30 to 240 min) in a double-blind randomized crossover design. Glucose (45 g), together with 5 g 3-O-methylglucose (3-OMG) and 20 MBq 99mTc-sulfur colloid (total volume 200 mL), was given intraduodenally (t = 0–60 min; 3 kcal/min). Duodenal motility and flow were measured using a combined manometry-impedance catheter and small intestinal transit using scintigraphy. In both groups, duodenal pressure waves and antegrade flow events were fewer, and transit was slower with exenatide, as were the areas under the curves for serum 3-OMG and blood glucose concentrations. Insulin concentrations were initially lower with exenatide than with saline and subsequently higher. Nausea was greater in both groups with exenatide, but suppression of small intestinal motility and flow was observed even in subjects with little or no nausea. The inhibition of small intestinal motor function represents a novel mechanism by which exenatide can attenuate postprandial glycemia.